Three‐dimensional echocardiography demonstrates a skewered left ventricular thrombus in a patient with a heart transplant. Issue 12 (18th October 2018) - Gannon, Michael P.; Saba, Shahryar G.; Hirsh, Benjamin J.; Halperin, Jonathan L.; Garcia, Mario J.; Pinney, Sean P.; Goldman, Martin E.
Abstract : A left ventricular (LV) false tendon is a frequently visualized structure in echocardiography with unclear clinical significance. We present the case of a false tendon serving as a nidus for thrombus in a post‐orthotopic heart transplantation patient. Three‐dimensional transthoracic echocardiography (3DTTE) was utilized to visualize a LV mass and facilitate its identification as a thrombus as well as the surrounding structures. Using datasets from 3DTTE, the lack of ventricular wall attachment and circumferential formation of the thrombus around the false tendon was identified. Serial imaging demonstrated resolution of the thrombus with anticoagulation.